2019
DOI: 10.1158/1078-0432.ccr-18-1222
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-dependent Tissue Factor Suppression Contributes to the Reduced Malignancy of IDH1-mutant Gliomas

Abstract: Purpose: Gliomas with isocitrate dehydrogenase 1 mutations (IDH1 mut) are less aggressive than IDH1 wild-type (IDH1 wt) gliomas and have global genomic hypermethylation. Yet it is unclear how specific hypermethylation events contribute to the IDH1 mut phenotype. Previously, we showed that the gene encoding the procoagulant tissue factor (TF), F3, is among the most hypermethylated and downregulated genes in IDH1 mut gliomas, correlating with greatly reduced thrombosis in patients with IDH1 mut glioma. Because T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…Importantly, our models retain R132H IDH1 heterozygosity and efficient production of 2HG 79 . In vitro cultures derived from these tumors either died or led to depletion of the wildtype IDH1 allele, in line with previous reports 49,80 , suggesting that IDH1mut gliomas require components of the brain microenvironment to maintain their growth. Importantly, our fully annotated cohort displays a wide variety of genetic features not recapitulated in other models (e.g., EGFR and PDGFRA amplification), thus reflecting the wide inter-patient heterogeneity of high-grade gliomas.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, our models retain R132H IDH1 heterozygosity and efficient production of 2HG 79 . In vitro cultures derived from these tumors either died or led to depletion of the wildtype IDH1 allele, in line with previous reports 49,80 , suggesting that IDH1mut gliomas require components of the brain microenvironment to maintain their growth. Importantly, our fully annotated cohort displays a wide variety of genetic features not recapitulated in other models (e.g., EGFR and PDGFRA amplification), thus reflecting the wide inter-patient heterogeneity of high-grade gliomas.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, we found that gliomas with mutations in isocitrate dehydrogenase 1 or IDH2 (collectively "IDH mut ") hypermethylate the early coding region of F3 and suppress its transcription, correlating with less flTF-MV production, less risk of VTE, and less aggressive behavior [116,117]. This appears to be unique to IDH mut gliomas, as other IDH mut cancers, like cholangiocarcinoma and acute myeloid leukemia, neither hypermethylate F3 nor suppress TF production [51,116].…”
Section: Regulation Of Tissue Factor Expressionmentioning
confidence: 78%
“…However, the response of cancers to TF likely depends on their molecular background. For example, we found that GBM cells with driver mutations in EGFR are far more dependent on endogenous TF for cell proliferation than GBM cells with driver mutations in NF1 [116].…”
Section: Tumor Angiogenesismentioning
confidence: 93%
See 1 more Smart Citation
“…Mutations in KRAS have been associated with increased tumor tissue factor expression in CRC and lung cancer [ 72 , 73 ]. Mutations in IDH1 led to hypermethylation of the F3 promoter of the tissue factor gene leading to decreased expression and may explain the decreased risk of VTE in primary brain cancer patients with mutant IDH1 [ 42 , 74 ]. Inflammation is known to induce a prothrombotic state and might play a role in cancer associated VTE [ 75 , 76 ].…”
Section: Potential Mechanisms Of Increased Thrombotic Riskmentioning
confidence: 99%